Numerical simulation study of power-frequency exposure to driving windings of electromagnetic suspension high-speed maglev trains - Pan, Qiangqiang; Lu, Mai (Radiation protection dosimetry, 2025)
As a potential mode of future passenger transport, the electromagnetic environment inside maglev trains is directly related to the safety and health of passengers. To study the electromagnetic exposure risk within the maglev train compartment, numerical models were established in this paper for the maglev track's long stator three-phase drive windings (serving as radiation sources), as well as for the train body and simplistic human body models representing passengers. The exposure levels of 50 Hz three-phase symmetrical current electromagnetic fields (EMFs) were numerically calculated for passengers positioned within the carriage. The numerical simulations focused on passengers' electromagnetic exposure resulting from the leakage of 50 Hz EMFs within the carriage and compared the results with established electromagnetic exposure limit guidelines. The findings indicated that the long stator three-phase drive windings generate electromagnetic leakage within the carriage, especially near the windows. Electromagnetic exposure levels vary, with passengers close to the windows experiencing more pronounced effects. Within the carriage, the maximum values of magnetic flux density (|B|) and induced electric field strength (|E|) for passengers' heads are ⁓0.59 μT and 337 μV/m, respectively. For passengers' torsos, the maximum values are ⁓1.53 μT for |B| and 57.8 μV/m for |E|. Passengers seated near the window exhibit higher values of |E| for their heads and higher values of |B| for their torsos. However, all of these values are well below the electromagnetic exposure limits (50 Hz) set by the International Commission on Non-Ionizing Radiation Protection. These findings provide valuable reference data for studying extremely low-frequency EMF exposure dosimetry in electromagnetic suspension high-speed maglev train systems.